Multiple Symbolism of Information and Communication Technology (ICT) in Academia: A Case Study of Technical Vocational Education and Training Institutions in Cape Town, South Africa - Van Der Poll, Arthur Emil (Cape Peninsula University of Technology, 2015)
Thesis submitted in fulfilment of the requirements for the degree Master of Technology: Information Technology in the Faculty of Informatics and Design at the Cape Peninsula University of Technology === It is well recognised that Information and Communication Technology (ICT) can enhance the quality of teaching and learning in tertiary education. Similarly, research has uncovered a range of factors that impede the successful adoption of digital technology for educational purposes. It remains unclear, furthermore, how educators in institutions of higher learning negotiate and frame their experiences with technology, and how this implicates the teaching and learning process. In this thesis, I will examine this problem, with particular focus on educators from Technical Vocational Education and Training (TVET) institutions in the Western Cape of South Africa. In addressing the research problem, I use symbolic interactionism as analytic framework to unpack and reconstruct the meaningful engagement with technology. Understanding the multiple symbolic meanings that arise from interactions with technology can illuminate the diverse and nuanced perspectives that underpin the use of ICT in teaching and learning. A symbolic interactionist lens can shed further light on the matter of adoption, and allow this research study to make a practical contribution to the introduction of ICT tools in TVETs. To elicit and interpret the multiple meanings that TVET educators associate with ICT, I will employ photo-elicitation methodology, observation and fieldnotes, and self-reflection. Photo-elicitation involves participants taking photographs along the line of inquiry (e.g. the benefit of using technology to teach), after which they undergo a reflexive interview in which they reflect on the meanings of the photographs they have taken. I will couple direct participant observation (documented in field notes) with symbolic interactionism and photo-elicitation to contribute to the production of meaningful data. Finaly, I will apply guidelines of self-reflection by compiling a reflective journal. Self-reflection will allow me to reflect on my own thoughts about the social phenomenon under study and will enable me to understand how my own behaviour may affect the inquiry. The meanings that emerged from the data were grouped into interactionist themes through which the engagement with technology is framed and understood. Educators are generally appreciative of the support and creative capacities that ICT provides to teaching and learning. They are however frustrated with their own inability to fully understand technology and the lack of support from government and institutional decision makers. Despite educators’ struggles with ICT, they are determined to overcome challenges. These themes can be useful in the repositioning of technology for education in TVETs, and can support implementers and policymakers in more effective application.